2009
DOI: 10.1128/mcb.01385-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Molybdoflavoenzyme Aldehyde Oxidase Homolog 2 in the Biosynthesis of Retinoic Acid: Generation and Characterization of a Knockout Mouse

Abstract: The mouse aldehyde oxidase AOH2 (aldehyde oxidase homolog 2) is a molybdoflavoenzyme. Harderian glands are the richest source of AOH2, although the protein is detectable also in sebaceous glands, epidermis, and other keratinized epithelia. The levels of AOH2 in the Harderian gland and skin are controlled by genetic background, being maximal in CD1 and C57BL/6 and minimal in DBA/2, CBA, and 129/Sv strains. Testosterone is a negative regulator of AOH2 in Harderian glands. Purified AOH2 oxidizes retinaldehyde int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
56
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 76 publications
1
56
1
Order By: Relevance
“…Observed interindividual variability is likely caused by the differences in the expression levels of human AO or by a number of single nucleotide polymorphisms recently observed in the human AOX1 gene (Hartmann et al, 2012). The relatively robust activity of AO in the human skin, despite the differences in donor demographics and anatomic region of the skin, may be related to the physiologic role of AO in the metabolism of endogenous retinoids (Tomita et al, 1993;Graessler and Fischer, 2007;Terao et al, 2009). A recent study in AO homolog 2 -/ -knockout mice observed thickening of the epidermis in basal conditions and after UV light exposure, probably triggered by local deficiency of all-trans retinoic acid (Terao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Observed interindividual variability is likely caused by the differences in the expression levels of human AO or by a number of single nucleotide polymorphisms recently observed in the human AOX1 gene (Hartmann et al, 2012). The relatively robust activity of AO in the human skin, despite the differences in donor demographics and anatomic region of the skin, may be related to the physiologic role of AO in the metabolism of endogenous retinoids (Tomita et al, 1993;Graessler and Fischer, 2007;Terao et al, 2009). A recent study in AO homolog 2 -/ -knockout mice observed thickening of the epidermis in basal conditions and after UV light exposure, probably triggered by local deficiency of all-trans retinoic acid (Terao et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…To our best knowledge, this is the first report of AO enzyme activity in the human skin. Terao et al (2009) recently reported activity of AO homolog 2 in the skin of mice, whereas Ueda et al (2005) investigated AO-catalyzed reduction of nitro-polycyclic aromatic hydrocarbons in skin samples from hamster, rabbit, guinea pig, mouse, and rat. Although the expression of AO was also reported in human adipose tissue (Weigert et al, 2008), the underlying fat was carefully removed from tested human skin samples, thus eliminating the possibility for a misinterpretation of results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AOX4 is highly presented in the Harderian gland and skin of mice, is absent in humans (Garattini et al, 2009;Terao et al, 2009). Evaluation of extrahepatic metabolism, which shows species differences, may increasingly improve the predictability of AO metabolism in human.…”
Section: Discussionmentioning
confidence: 99%
“…Adding to the frustration, XOR tissue-specific conditional knockouts are currently not available while global XOR −/− and XOR +/− mice experience alterations in nutrient absorption and elevated plasma hypoxanthine levels resulting in death from kidney failure before 6 weeks of age [9,10]. As for AO, there is only one report demonstrating successful knockout of one homologue of AO (aldehyde oxidase homologue 2, Aoh2) expressed primarily in the epithelium [11]. The current absence of knockout strategies to interrogate these molybdopterin enzymes has relegated investigators to employ pharmacologic means to conduct proof of principle experimentation regarding contributory roles mediating the effects of treatment.…”
Section: Introductionmentioning
confidence: 99%